FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN ATRAKSI WISATA OLEH WISATAWAN MILENIAL SELAMA BERWISATA DI BALI - Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020), 2020)
Millennial tourists have very promising potential for Bali tourism. This study was conducted to help Bali tourism stake holders in providing tourist attractions that suit their tastes with the millennial to be able to seize the millennial tourist market. This study uses descriptive quantitative data analysis which is processed using the SPSS 17.0 for windows. The sample was determined purposively amounting to 100 respondents. Data collection techniques using observation, questionnaires, and literature studies. Data analysis techniques are the validity test, reliability test, and factor analysis. The factors that influence the decision to purchase tourist attractions by millennial tourists during a tour in Bali, there are six factors formed with 22 variables. The first factor is a psychological factor consisting of 4 factors. The second factor is the price factor which consists of 5 factors. The third factor is the recommendation factor consisting of 6 factors. The fourth factor is a personal factor consisting of 4 factors. The fifth factor is the social factor which consists of 2 factors. The sixth factor is the external factor consists of 1 factor, namely the discussion of attractions interest. The dominant factor influencing the decision to purchase tourist attractions by millennial tourists during a tour in Bali is the first factor named psychological factor. Psychological factors, outperform other factors with a percentage of variance of 32,329% and an eigenvalue of 7,112. Therefore, psychological factors are the main factors that influence the decision to purchase tourist attractions by millennial tourists during a tour in Bali.